Deodorizing ceramic plate for tea drying box and preparation method of deodorizing ceramic plate
By preparing a complex composition of odor removal ceramic plate, the problem of poor deodorization effect of traditional tea drying boxes is solved, and more efficient deodorization effect and better mechanical properties are achieved.
Patent Information
- Application Number
- CN202411460587.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-07
AI Technical Summary
During the hot air drying process of traditional tea drying boxes, the tea smell and impurities mixed in the hot air will penetrate deep into the gaps of the drying box and adhere to the inner wall, resulting in poor deodorization effect.
A deodorizing ceramic plate for tea drying box is adopted, and its composition includes quartz, deodorizing particles, crosslinking agent, carbon nanofiber, magnesium oxide, sodium hydroxymethylcellulose, potassium feldspar, sodium silicate and kaolin , prepared by mixing, ball milling, molding, degumming and firing, a ceramic plate with excellent odor removal effect and good mechanical properties are formed.
It significantly improves the deodorization effect of the tea drying box, reduces the adhesion of tea smell and impurity odor, enhances the mechanical properties of the ceramic plate, and is suitable for the high-temperature and high-pressure environment of the tea drying box.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a deodorizing ceramic plate for a tea drying box and a preparation method thereof. Background Art
[0002] In the process of tea processing and production, both strip and curled tea need hot air drying in the later stage of processing. The tea drying box heats the tea at a certain temperature to reduce the moisture content of the tea. When the traditional hot air drying box is performing hot air drying, a large amount of hot air will be discharged from the exhaust port. At this time, the gas mixed with the smell of tea and impurities will gradually penetrate into the gap of the drying box, and will also adhere to the inner wall of the drying box as the drying progresses. Ceramic products are used in many industries due to their good density, strength, practicality and wear resistance. The application of ceramic products in the field of tea is gradually accepted by the industry. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a deodorizing ceramic plate for a tea drying box and a preparation method thereof, wherein the prepared ceramic tile has excellent deodorizing effect and good mechanical properties.
[0004] In order to achieve the above object, the present invention provides the following technical solutions: A deodorizing ceramic plate for a tea drying box comprises the following components in parts by weight: 20-30 parts of quartz, 10-20 parts of deodorizing particles, 20-30 parts of a cross-linking agent, 5-8 parts of carbon nanofibers, 6-8 parts of magnesium oxide, 10-12 parts of sodium hydroxymethyl cellulose, 15-20 parts of potassium feldspar, 5-8 parts of sodium silicate and 18-20 parts of kaolin.
[0005] A method for preparing a deodorizing ceramic plate for a tea drying box comprises the following steps: S1: quartz, deodorizing particles, cross-linking agent, carbon nanofiber, magnesium oxide, sodium hydroxymethyl cellulose, potassium feldspar, sodium silicate and kaolin are mixed, and the mixture is ball-milled through a 200-mesh sieve to obtain a mixture; S2: The mixed material obtained in step S1 is molded, degummed and fired, and naturally cooled to room temperature to obtain a deodorizing ceramic plate for a tea drying box.
[0006] Preferably, the method for preparing the deodorizing particles in step S1 comprises: Chitosan, cellulose nanofiber, graphene oxide dispersion, citric acid and ascorbic acid are mixed, heated and dried, sintered and ground to obtain deodorizing particles.
[0007] Preferably, the weight ratio of the chitosan, cellulose nanofibers, graphene oxide dispersion, citric acid and ascorbic acid is 1:1:1:2:2.
[0008] Preferably, the preparation method of the cross-linking agent is specifically as follows: xylitol, polyvinyl alcohol, carbon fiber and 30% hydrochloric acid by volume are mixed, and stirred at 30-40° C. for 3-4 hours to obtain a pre-cross-linking solution; The pre-crosslinking liquid and N,N-dihydroxyethyl-3-aminopropionic acid methyl ester are mixed in a weight ratio of 1:1, and stirred for 10-12 hours to obtain a crosslinking agent.
[0009] Preferably, the preparation method of N,N-dihydroxyethyl-3-aminopropionic acid methyl ester is as follows: 2,2'-dihydroxydiethylamine and anhydrous methanol are mixed and stirred until completely dissolved, methyl acrylate is added and stirred for 1-2 hours, and the reaction is stirred at 30-40°C for 3-4 hours, and the mixture is distilled and dried under reduced pressure to obtain N,N-dihydroxyethyl-3-aminopropionic acid methyl ester.
[0010] Preferably, the weight ratio of the 2,2'-dihydroxydiethylamine, anhydrous methanol and methyl acrylate is 1:3:1.
[0011] Preferably, the weight ratio of xylitol, polyvinyl alcohol, carbon fiber and hydrochloric acid is 1:2:2:4.
[0012] Preferably, the drying temperature is 40-60° C. and the drying time is 12-24 hours.
[0013] Preferably, the molding, degumming and sintering of the molding material in step S2 specifically includes: The molding temperature is 300-400°C, the molding pressure is 5-6Mpa, and the molding time is 8-10s; the degumming temperature is 600-700°C; the sintering temperature is 1500-1540°C, the time is 10-12h, and the heat preservation is 8-10h.
[0014] The N,N-dihydroxyethyl-3-aminopropionic acid methyl ester of the present invention has a large number of active functional groups on the side chain and has a relatively low molecular weight. The viscosity of the pre-crosslinking liquid is gradually reduced during the stirring process, so that the N,N-dihydroxyethyl-3-aminopropionic acid methyl ester can effectively penetrate into the pre-crosslinking liquid and be crosslinked and filled into the mixed system. Due to its high reaction activity, it is easy to produce multi-point crosslinking and play a good filling role, thereby making the particles closely connected, the collision between the particles is intensified to increase the internal friction of the system, further improve the viscosity of the system, and form a three-dimensional network structure with a larger specific surface area. The deodorizing particles further act as a three-dimensional nano support skeleton in the three-dimensional network structure to prevent agglomeration between components. The deodorizing particles and carbon nanofibers are filled in the pores of the three-dimensional network structure to reduce the gap between the components, while increasing the specific surface area and contact area of the deodorizing particles and the carbon nanofibers for adsorption, improving the adsorption capacity, and being able to increase the compactness of the ceramic components and enhance the mechanical properties. DETAILED DESCRIPTION
[0015] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In addition, it is specifically stated that the raw materials and equipment of the present invention can be obtained from commercial sources, and no longer listed one by one. Among them, the raw materials of the present invention can be obtained from commercial sources and are well known to those skilled in the art. Embodiment 1:
[0016] A deodorizing ceramic plate for a tea drying box comprises the following components in parts by weight: 20 parts of quartz, 10 parts of deodorizing particles, 20 parts of a cross-linking agent, 5 parts of carbon nanofibers, 6 parts of magnesium oxide, 10 parts of sodium hydroxymethyl cellulose, 15 parts of potassium feldspar, 5 parts of sodium silicate and 18 parts of kaolin.
[0017] A method for preparing a deodorizing ceramic plate for a tea drying box comprises the following steps: S1: quartz, deodorizing particles, cross-linking agent, carbon nanofiber, magnesium oxide, sodium hydroxymethyl cellulose, potassium feldspar, sodium silicate and kaolin are mixed, and the mixture is ball-milled through a 200-mesh sieve to obtain a mixture; S2: The mixture obtained in step S1 is molded, degummed and fired, wherein the molding temperature is 300°C, the molding pressure is 5Mpa, and the molding time is 8s; the degumming temperature is 600°C; the firing temperature is 1500°C, the time is 10h, and the heat preservation is 8h, and it is naturally cooled to room temperature to obtain a deodorizing ceramic plate for a tea drying box.
[0018] The method for preparing the deodorizing particles in step S1 includes: Chitosan, cellulose nanofibers, a graphene oxide dispersion with a concentration of 0.5 g / L, citric acid and ascorbic acid are mixed in a weight ratio of 1:1:1:2:2, stirred and dried at a drying temperature of 40° C. for 12 h, and ground to obtain deodorizing particles.
[0019] The preparation method of the crosslinking agent is as follows: xylitol, polyvinyl alcohol, carbon fiber and hydrochloric acid with a volume fraction of 30% are mixed in a weight ratio of 1:2:2:4, and stirred at 30° C. for 3 hours to obtain a pre-crosslinking solution; The pre-crosslinking liquid and N,N-dihydroxyethyl-3-aminopropionic acid methyl ester were mixed in a weight ratio of 1:1, and stirred for 10 hours to obtain a crosslinking agent.
[0020] The specific preparation method of N,N-dihydroxyethyl-3-aminopropionic acid methyl ester is as follows: 2,2'-dihydroxydiethylamine and anhydrous methanol are mixed and stirred until completely dissolved, and then methyl acrylate is added and stirred for 1 hour, and stirred and reacted at 30°C for 3 hours, and distilled and dried under reduced pressure to obtain N,N-dihydroxyethyl-3-aminopropionic acid methyl ester, wherein the weight ratio of 2,2'-dihydroxydiethylamine, anhydrous methanol and methyl acrylate is 1:3:1. Embodiment 2:
[0021] A deodorizing ceramic plate for a tea drying box comprises the following components in parts by weight: 30 parts of quartz, 20 parts of deodorizing particles, 30 parts of a cross-linking agent, 8 parts of carbon nanofibers, 8 parts of magnesium oxide, 12 parts of sodium hydroxymethyl cellulose, 20 parts of potassium feldspar, 8 parts of sodium silicate and 20 parts of kaolin.
[0022] A method for preparing a deodorizing ceramic plate for a tea drying box comprises the following steps: S1: quartz, deodorizing particles, cross-linking agent, carbon nanofiber, magnesium oxide, sodium hydroxymethyl cellulose, potassium feldspar, sodium silicate and kaolin are mixed, and the mixture is ball-milled through a 200-mesh sieve to obtain a mixture; S2: The mixture obtained in step S1 is molded, degummed and fired, wherein the molding temperature is 400°C, the molding pressure is 6Mpa, and the molding time is 10s; the degumming temperature is 700°C; the firing temperature is 1540°C, the time is 12h, and the heat preservation is 10h, and it is naturally cooled to room temperature to obtain a deodorizing ceramic plate for a tea drying box.
[0023] The method for preparing the deodorizing particles in step S1 includes: Chitosan, cellulose nanofibers, a graphene oxide dispersion with a concentration of 0.5 g / L, citric acid and ascorbic acid are mixed in a weight ratio of 1:1:1:2:2, stirred and dried at a drying temperature of 60° C. for 24 h, and ground to obtain deodorizing particles.
[0024] The preparation method of the crosslinking agent is as follows: xylitol, polyvinyl alcohol, carbon fiber and hydrochloric acid with a volume fraction of 30% are mixed in a weight ratio of 1:2:2:4, and stirred at 40° C. for 4 hours to obtain a pre-crosslinking solution; The pre-crosslinking liquid and N,N-dihydroxyethyl-3-aminopropionic acid methyl ester are mixed in a weight ratio of 1:1, and stirred for 10-12 hours to obtain a crosslinking agent.
[0025] The specific preparation method of N,N-dihydroxyethyl-3-aminopropionic acid methyl ester is as follows: 2,2'-dihydroxydiethylamine and anhydrous methanol are mixed and stirred until completely dissolved, and then methyl acrylate is added and stirred for 2 hours, and stirred and reacted at 40°C for 4 hours, and vacuum distilled and dried to obtain N,N-dihydroxyethyl-3-aminopropionic acid methyl ester, wherein the weight ratio of 2,2'-dihydroxydiethylamine, anhydrous methanol and methyl acrylate is 1:3:1. Embodiment 3:
[0026] A deodorizing ceramic plate for a tea drying box comprises the following components in parts by weight: 25 parts of quartz, 15 parts of deodorizing particles, 25 parts of a cross-linking agent, 6 parts of carbon nanofibers, 7 parts of magnesium oxide, 11 parts of sodium hydroxymethyl cellulose, 18 parts of potassium feldspar, 6 parts of sodium silicate and 19 parts of kaolin.
[0027] A method for preparing a deodorizing ceramic plate for a tea drying box comprises the following steps: S1: quartz, deodorizing particles, cross-linking agent, carbon nanofiber, magnesium oxide, sodium hydroxymethyl cellulose, potassium feldspar, sodium silicate and kaolin are mixed, and the mixture is ball-milled through a 200-mesh sieve to obtain a mixture; S2: The mixture obtained in step S1 is molded, degummed and fired, wherein the molding temperature is 350°C, the molding pressure is 5.5Mpa, and the molding time is 9s; the degumming temperature is 650°C; the firing temperature is 1520°C, the time is 11h, and the heat preservation is 9h, and it is naturally cooled to room temperature to obtain a deodorizing ceramic plate for a tea drying box.
[0028] The method for preparing the deodorizing particles in step S1 includes: Chitosan, cellulose nanofibers, a graphene oxide dispersion with a concentration of 0.5 g / L, citric acid and ascorbic acid are mixed in a weight ratio of 1:1:1:2:2, stirred and dried at a drying temperature of 50° C. for 18 h, and ground to obtain deodorizing particles.
[0029] The preparation method of the crosslinking agent is as follows: xylitol, polyvinyl alcohol, carbon fiber and hydrochloric acid with a volume fraction of 30% are mixed in a weight ratio of 1:2:2:4, and stirred at 35° C. for 3.5 hours to obtain a pre-crosslinking solution; The pre-crosslinking liquid and N,N-dihydroxyethyl-3-aminopropionic acid methyl ester are mixed in a weight ratio of 1:1, and stirred for 10-12 hours to obtain a crosslinking agent.
[0030] The specific preparation method of N,N-dihydroxyethyl-3-aminopropionic acid methyl ester is as follows: 2,2'-dihydroxydiethylamine and anhydrous methanol are mixed and stirred until completely dissolved, and then methyl acrylate is added and stirred for 1-2 hours, and stirred and reacted at 35°C for 3.5 hours, and vacuum distilled and dried to obtain N,N-dihydroxyethyl-3-aminopropionic acid methyl ester, wherein the weight ratio of 2,2'-dihydroxydiethylamine, anhydrous methanol and methyl acrylate is 1:3:1. Comparative Example 1:
[0031] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that no deodorizing particles and cross-linking agent are used, specifically: A deodorizing ceramic plate for a tea drying box comprises the following components in parts by weight: 20 parts of quartz, 5 parts of carbon nanofiber, 6 parts of magnesium oxide, 10 parts of sodium hydroxymethyl cellulose, 15 parts of potassium feldspar, 5 parts of sodium silicate and 18 parts of kaolin.
[0032] A method for preparing a deodorizing ceramic plate for a tea drying box comprises the following steps: S1: quartz, carbon nanofibers, magnesium oxide, sodium hydroxymethyl cellulose, potassium feldspar, sodium silicate and kaolin are mixed, and the mixture is ball-milled through a 200-mesh sieve to obtain a mixture; S2: The mixture obtained in step S1 is molded, degummed and fired, wherein the molding temperature is 300°C, the molding pressure is 5Mpa, and the molding time is 8s; the degumming temperature is 600°C; the firing temperature is 1500°C, the time is 10h, and the heat preservation is 8h, and it is naturally cooled to room temperature to obtain a deodorizing ceramic plate for a tea drying box.
[0033] The following is a mechanical property test of the ceramic plates obtained in Examples 1 to 3 of the present invention, Comparative Example 1, and a common ceramic plate (purchased from Jingdezhen Welland Ceramics Co., Ltd.), and assembled into a tea drying box for a deodorization test. The test results are shown in Table 1.
[0034] Mechanical strength: Tested in accordance with GB / T 4740-1999.
[0035] Deodorization test: trimethylamine and methyl mercaptan gas were introduced into an 80L well-sealed tea drying box to make the initial concentration of trimethylamine and methyl mercaptan 2-12 mg / m 3 The air was circulated and ventilated for 2 minutes, and the initial concentration of the sample was collected; then the tea drying box was turned on and operated normally for 2 hours, and the gas concentration after 2 hours of operation was collected. Each gas was tested repeatedly for multiple times, and the data was selected. The deodorization rate was calculated as [(initial gas concentration - end gas concentration) / initial gas concentration] × 100%.
[0036] Table 1 Test data of Examples 1-3, commercially available ceramic plates and Comparative Example 1 It can be seen from the above table that the deodorizing effects of Examples 1-3 are improved compared with those of Comparative Example 1 and commercially available ceramic plates, and the Examples 1-3 have good compressive strength, fracture toughness and flexural strength.
[0037] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A deodorizing ceramic plate for a tea drying box, characterized in that: The invention comprises the following components in parts by weight: 20-30 parts of quartz, 10-20 parts of deodorizing particles, 20-30 parts of cross-linking agent, 5-8 parts of carbon nanofiber, 6-8 parts of magnesium oxide, 10-12 parts of sodium hydroxymethyl cellulose, 15-20 parts of potassium feldspar, 5-8 parts of sodium silicate and 18-20 parts of kaolin.
2. A method for preparing the deodorizing ceramic plate for a tea drying box as claimed in claim 1, characterized in that: The following steps are involved: S1: quartz, deodorizing particles, cross-linking agent, carbon nanofiber, magnesium oxide, sodium hydroxymethyl cellulose, potassium feldspar, sodium silicate and kaolin are mixed, and the mixture is ball-milled through a 200-mesh sieve to obtain a mixture; S2: The mixed material obtained in step S1 is molded, degummed and fired, and naturally cooled to room temperature to obtain a deodorizing ceramic plate for a tea drying box.
3. The method for preparing the deodorizing ceramic plate for a tea drying box according to claim 2, characterized in that: The method for preparing the deodorizing particles in step S1 comprises: Chitosan, cellulose nanofibers, graphene oxide dispersion, citric acid and ascorbic acid are mixed, stirred, dried and ground to obtain deodorizing particles.
4. The method for preparing the deodorizing ceramic plate for a tea drying box according to claim 3, characterized in that: The weight ratio of the chitosan, the cellulose nanofiber, the graphene oxide dispersion, the citric acid and the ascorbic acid is 1:1:1:2:
2.
5. The method for preparing the deodorizing ceramic plate for a tea drying box according to claim 2, characterized in that: The preparation method of the cross-linking agent is specifically as follows: xylitol, polyvinyl alcohol, carbon fiber and hydrochloric acid with a volume fraction of 30% are mixed, and stirred at 30-40° C. for 3-4 hours to obtain a pre-cross-linking solution; The pre-crosslinking liquid and N,N-dihydroxyethyl-3-aminopropionic acid methyl ester are mixed in a weight ratio of 1:1, and stirred for 10-12 hours to obtain a crosslinking agent.
6. The method for preparing the deodorizing ceramic plate for a tea drying box according to claim 5, characterized in that: The preparation method of N,N-dihydroxyethyl-3-aminopropionic acid methyl ester is specifically as follows: 2,2'-dihydroxydiethylamine and anhydrous methanol are mixed and stirred until completely dissolved, methyl acrylate is added and stirred for 1-2 hours, and stirred and reacted at 30-40°C for 3-4 hours, and vacuum distilled and dried to obtain N,N-dihydroxyethyl-3-aminopropionic acid methyl ester.
7. The method for preparing the deodorizing ceramic plate for a tea drying box according to claim 6, characterized in that: The weight ratio of the 2,2'-dihydroxydiethylamine, anhydrous methanol and methyl acrylate is 1:3:
1.
8. The method for preparing the deodorizing ceramic plate for a tea drying box according to claim 5, characterized in that: The weight ratio of the xylitol, polyvinyl alcohol, carbon fiber and hydrochloric acid is 1:2:2:
4.
9. The method for preparing the deodorizing ceramic plate for a tea drying box according to claim 3, characterized in that: The drying temperature is 40-60°C and the drying time is 12-24h.
10. The method for preparing ceramic tiles using waste materials as claimed in claim 2, characterized in that: The step S2 of molding, degumming and sintering the molding material specifically includes: The molding temperature is 300-400°C, the molding pressure is 5-6Mpa, and the molding time is 8-10s; the degumming temperature is 600-700°C; the sintering temperature is 1500-1540°C, the time is 10-12h, and the heat preservation is 8-10h.
Citation Information
Patent Citations
High efficiency flue gas purification device
CN109603521A
Ultrathin rock plate as well as preparation method and application thereof
CN112851295A
High-strength and high-whiteness ceramic product and processing technology thereof
CN114477951A
Infrared drying equipment
CN205593348U
Tea leaf baking machine
CN208836947U